A study of knowledge and practice of menstrual hygiene among adolescent school girls in rural and urban field practice area of RajaRajeswari Medical College and Hospital, Bangalore, India - Kailasraj, Kanchanaganga Hassan; Basavaraju, Vidya; Kumar, Jayanth; Manjunatha, Shashikala (International Journal Of Community Medicine And Public Health, 2020)
Background: The word adolescent is derived from Latin word adolescence which means to grow into maturity. Adolescence is a period of transition from childhood to adulthood. WHO has defined adolescence as the age group 10-19 years. These are formative years when maximum amount of physical, psychological, developmental and behavioral changes take place. In India adolescent girls accounts for a little more than one- fifth of the population. The onset on menstruation is one of the most important changes occurring among the girls during the adolescent years. The event of menarche may be associated with taboos and myths existing in our traditional society which has a negative implication for women’s health, particularly their menstrual hygiene. Women having better knowledge regarding menstrual hygiene and safe practices are less vulnerable to reproductive tract infections. Methods: This was a cross-sectional descriptive study. The sample size of 184 is obtained in each group and rounded off to 190 (urban and rural schools). The duration of the study was for 5 months among adolescent high school girls in randomly selected schools. Results: The mean age of urban girls was 12.87±0.94 years whereas rural girls it was 12.85±0.86 years. Among 380 study subjects 43.4% were aware about menstruation before attaining menarche, 62.4% were aware that menstruation is a natural process. Majority of study subjects (58.9%) were using sanitary pads during menstruation and 46.8% of study subject’s changes absorbents twice a day. Conclusion: Knowledge and practice regarding menstrual hygiene among adolescent high school girls is better in rural area as compared to urban adolescent high school girls.